Gamifikasi Sepak Bola untuk Tingkatkan Keterlibatan dan Kinerja Motorik Siswa di SD Negeri 047176 Sirumbia - Janwar Frihasan Sinuraya; Julius Boy Nesra Basgimata Barus; Agavetra Tarigan; Egin Ginting (MAN Insan Cendekia Jambi, 2025)
This research is motivated by the problem of low student active participation and suboptimal motor skill achievement in physical education learning, particularly soccer material in elementary schools. The conventional approach applied so far is considered ineffective in arousing student interest and motivation to learn. This condition indicates the urgency of innovative learning strategies that can create a more interesting and interactive learning atmosphere. Gamification, as a strategy that integrates game elements in an educational context, is a potential alternative solution. The purpose of this study was to analyze the effectiveness of implementing gamification in soccer learning on improving student engagement and motor performance at SD Negeri 047176 Sirumbia. The method used was quantitative with a quasi-experimental design. Data collection instruments included observations of student engagement, soccer motor skills tests, documentation, and supporting interviews. The results showed that gamification significantly increased student active engagement during learning and had a positive impact on motor performance, including coordination, agility, and movement control. In conclusion, gamification has been proven effective in improving student participation and motor skills. The implications of this research indicate that the integration of gamification in physical education can be an innovative and applicable strategy to create more meaningful and efficient learning at the elementary school level.